Evaluation of Variance Inflation Factors in Regression Models Using Latent Variable Modeling Methods. (October 2019) - Marcoulides, Katerina M.; Raykov, Tenko
A procedure that can be used to evaluate the variance inflation factors and tolerance indices in linear regression models is discussed. The method permits both point and interval estimation of these factors and indices associated with explanatory variables considered for inclusion in a regression model. The approach makes use of popular latent variable modeling software to obtain these point and interval estimates. The procedure allows more informed evaluation of these quantities when addressing multicollinearity-related issues in empirical research using regression models. The method is illustrated on an empirical example using the popular software M plus . Results of a simulation study investigating the capabilities of the procedure are also presented.